The Impact of Total Quality Management on Patient Satisfaction with Mediating Role of Perceived Service Quality of Healthcare - Bushra Khalil Dar; Rabia Majeed; Shakeel Khan; Muhammad Imad Khan (International Journal of Business and Economic Affairs, 2023)
This study aims to investigate the impact of total quality management (TQM) on patient satisfaction (PS). In addition to this mediating role of perceived service quality (PSQ) for the same has also been studied.The data has been analyzed using regression and correlation analysis on the primary data collected through a close-ended questionnaire. The data from 154 patients in different hospitals in Rawalpindi have been collected by filling up the online Google form. All the items in the questionnaire were based on a five-point Likert scale ranging from strongly agree to strongly disagree. Results of the study indicated an insignificant relationship between total quality management and patient satisfaction. Furthermore, the significant indirect effect of TQM on PS through the mediating role of PSQ further supports the hypothesis. On the basis of the findings of this study, it is suggested that healthcare managers should opt for oriented management strategies for patient satisfaction. Good quality healthcare services result in boosting patient satisfaction. Additionally, to meet the patient’s expectations both the technical as well as functional competencies of the healthcare service providers ought to be enhanced. The contribution of this study is the establishment of the indirect effect of total quality management on patient satisfaction through the mediating effect of perceived service quality.